Buy‐now‐pay‐later: Hazards to human and planetary health from plastics production, use and waste. (18th November 2021) - Symeonides, Christos; Brunner, Manuel; Mulders, Yannick; Toshniwal, Priyanka; Cantrell, Matthew; Mofflin, Louise; Dunlop, Sarah
Abstract : More than 8 billion tonnes of plastic were produced between 1950 and 2015, that is 1 tonne for every man, woman and child on our planet. Global plastic production has been growing exponentially with an annual growth rate of 8.4% since 1950, equating to approximately 380 million tonnes per annum. A further 50 kg of plastic is now being produced for each person every year with production continuing to accelerate. Here, we discuss the human and planetary health hazards of all that plastic. We consider each step in the journey of these complex and pervasive industrial materials: from their synthesis predominantly from fossil fuel feedstocks, through an often‐brief consumer use as plastic products, and onto waste streams as fuel, permanent landfill or as unmanaged waste in our environment, food, air and bodies.